Rural prevalence of type 2 diabetes mellitus: A cross sectional study - Rathod, Hetal K; Darade, Sanjay S; Chitnis, Uday B; Bhawalkar, Jitendra S; Jadhav, Sudhir L; Banerjee, Amitav (Journal of Social Health and Diabetes, 2014)
Background: Recent studies in India indicate rising trends of diabetes even in rural areas. Continuous monitoring of the diabetes situation is required by repeated cross sectional studies in different parts of the country both urban rural to plan control measures. Aim: To estimate the prevalence of Type 2 diabetes in a sample of rural population and explore associations between diabetes and known risk factors. Materials and Methods: A cross sectional study was carried out in 3 villages in the rural field practice area of a medical college in Pune, India. All eligible adults of both genders were included and screened for diabetes by house to house survey. A total of 1000 subjects were examined. Physical examination included measuring height, weight, and waist hip ratio. Blood glucose was estimated using glucometer. Family history of diabetes was also elicited. Data was analysed by descriptive statistics using proportions with 95% confidence intervals. Various associations were explored using using Odds Ratio with 95% confidence intervals as applicable. Results: The prevalence of diabetes mellitus was 9.1% (91/1000; 95% CI 7.4, 11). Most cases of newly detected diabetics were in the age group 36 - 40 years. There was no association between gender and diabetes (OR = 1.38, 95% CI 0.88, 2.17). Overweight status was associated with diabetes: 38.5% (35/91) of diabetics were overweight compared to 18.6% (169/909) of non-diabetics (OR = 2.74, 95% CI 1.69, 4.41). Similarly abnormal waist hip ratio was associated with diabetes: 47.25% (43/91) of diabetics had high waist hip ratio compared with 29.59% (269/909) of non-diabetics (OR = 2.13, 95% CI 1.35, 3.37). Also family history was strongly associated with diabetes: 27.5% (25/91) of diabetics gave positive family history compared with 9.4% (85/909) of non-diabetics (OR = 3.67, 95% CI = 2.13, 6.30). Conclusion: The burden of diabetes was present in the rural population studied. The associated known risk factors were also prevalent and showed strong relationship with diabetes. Diabetes mellitus erstwhile thought to be a disease of urban life appears to be equally prevalent in the rural setting.
Keywords: India; Type 2 diabetes; risk factors; rural population